THE RECENT EMERGENCE OF WHITE SUPREMACIST SOCIETY IN THE UNITED STATES: A CRITICAL DISCOURSE ANALYSIS IN MODERN KU KLUX KLAN - Hussna, Aprilia Zainatul (UI Scholars Hub, 2023)
This paper examines the discourse in Loyal White Knights of the Ku Klux Klan, one of the most recently active chapters of the Ku Klux Klan (KKK). With the flyering (spreading flyers/pamphlets) incidents that spiked during and in the aftermath the Charlottesville protests in 2017, in the few recent years some of the more active chapters of KKK have steadily distributed the flyers in the United States. Recognizing the Ku Klux Klan’s historical role within the white supremacist movement and its participation in the Unite the Right rally, it is important to understand the meaning behind the discourse and the social act. This is a qualitative and descriptive analysis done on the basis of Fairclough’s three-dimensional framework (Fairclough, 1995) and Gunther Kress and Theo van Leeuwen’s theory (2006) derived from Halliday’s systemic functional linguistics. It is found from the analysis that the KKK tries to appeal to the audience for their sympathy, courage, and pride.